Isolamento e identificação de compostos ativos de Vismia guianensis com potencial inseticida contra formigas cortadeiras - Pio, Yara Polianna Fonseca (Universidade Federal de São Carlos, 2024)
Vismia guianensis, also known as "pau lacre," is chemically notable for the presence of a variety of secondary compounds in its organs, including roots, bark, and leaves. These compounds have garnered interest due to their biological and pharmacological potential. This study aimed to explore Vismia guianensis as a promising source of natural insecticides for combating the ant species Atta sexdens and to synthesize copper complexes from the isolated compounds. Using extraction techniques and advanced analytical methods, six novel benzophenones were isolated from the species, four of which (Vismiaguienones 1, 2, 3, and 6) are novel to the literature, along with a common anthraquinone in the genus, totaling seven isolated compounds and a copper anthraquinone complex (CuF 1:2). The study examined three extract matrices from different species (Vismia guianensis, Mansoa alliacea, and Tabernaemontana angulata), finding that only the Vismia guianensis extract (PLF) exhibited insecticidal activity against Atta sexdens, as did fractions F1 and F2, leading to compound isolation. Only two compounds, the anthraquinone (compound 7) and Vismiaguienone 4, did not exhibit activity. Regarding the complex and the ligand, complexation effectively increased the mortality rate of the leaf-cutting ants, with the ligand showing 66% mortality and the complex achieving 92%, representing an effective alternative to synthetic insecticides. Thus, this research directly contributes to the development of more sustainable strategies for managing leaf-cutting ants of the species Atta sexdens, as well as enhancing the chemotaxonomic knowledge of the species Vismia guianensis.
Isolation and identification of compounds Vismia guianensis assets with potential insecticide against cutter ants
Isolation and identification of compounds Vismia guianensis assets with potential insecticide against cutter ants
Keywords: Formigas cortadeiras; Vismia guianensis; Vismiaguienona; Benzofenonas preniladas; Cutter ants; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS